Catabolite repression control protein antagonist, a novel player in Pseudomonas aeruginosa carbon catabolite repression control - Sonnleitner, Elisabeth; Bassani, Flavia; Cianciulli Sesso, Anastasia; Brear, Paul; Lilic, Branislav; Davidovski, Lovro; Resch, Armin; Luisi, Ben F.; Moll, Isabella; Bläsi, Udo (Frontiers in Microbiology, 2023)
In the opportunistic human pathogen Pseudomonas aeruginosa (Pae), carbon catabolite repression (CCR) orchestrates the hierarchical utilization of N and C sources, and impacts virulence, antibiotic resistance and biofilm development. During CCR, the RNA chaperone Hfq and the catabolite repression control protein Crc form assemblies on target mRNAs that impede translation of transcripts involved in uptake and catabolism of less preferred C sources. After exhaustion of the preferred C-source, translational repression of target genes is relieved by the regulatory RNA CrcZ, which binds to and acts as a decoy for Hfq. Here, we asked whether Crc action can be modulated to relieve CCR after exhaustion of a preferred carbon source. As Crc does not bind to RNA per se, we endeavoured to identify an interacting protein. In vivo co-purification studies, co-immunoprecipitation- and biophysical assays revealed that Crc binds to Pae strain O1 protein PA1677. Our structural studies support bioinformatics analyses that PA1677 belongs to the isochorismatase-like superfamily. Ectopic expression of PA1677 resulted in de-repression of Hfq/Crc controlled target genes, while in the absence of the protein, an extended lag phase is observed during diauxic growth on a preferred and a non-preferred carbon source. This observations indicate that PA1677 acts as an antagonist of Crc that favours synthesis of proteins required to metabolize non-preferred carbon sources. We present a working model wherein PA1677 diminishes the formation of productive Hfq/Crc repressive complexes on target mRNAs by titrating Crc. Accordingly, we propose the name CrcA (catabolite repression control protein antagonist) for PA1677.